Framework para implementação de serviços transmissores de vídeos voltados a PCS e dispositivos móveis, perceptivo à mudança contextual de localização - Jardim, Fernando de Moraes (2004)
With the progress of the technology in data transmission area and the fact of computers be present more and more in several equipments, like PDAs (Personal Digital Systems), mobile telephones, cars, refrigerators, etc, it becomes necessary to establish a standart communication protocol among these several computers. The work presented in this monograph has as objective to define a necessary infrastructure to implementations of videos transmission services for mobile devices (PDAs and mobile telephones) with transparent change of location context. This context change represents the change of physical atmosphere of the proposed system user. The idea is that the user continues to watch a video (in a mobile device) when he leaves the place where he was watching it. A framework was modeled and implemented to detect change of physical atmosphere destined to videos transmission services directed to mobile devices. High degree of mobility and transparency is characteristic of Ubiquitous Computation (Computation new moment - Weiser). For a theoretical basement was carried through a research on the concepts related with Ubiquitous Computation, mobile devices and video transmissions. This work was developed in the Network and Distributed Systems Laboratory of São Carlos Federal University - UFSCar.